Analiza wpływu wyboru metody znieczulenia pacjenta na koszty szpitala - Nieplowicz, Maria; Tlolka, Rudolf (Analysis of the Choice's Influence of Patient's Anaesthesia on Hospital Costs, 2008)
The aim of the paper is to demonstrate differences between commonly used methods of anaesthesia and to point out validity of choice of the selected method of anaesthesia, while going by for patients benefit and beared costs optimization of Health Care Unit.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 32, s. 72-86